IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH DEBATE TECHNIQUE - Reni Rosianna Lumbangaol; Muhammad Rizki Mazali (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The study is aim to find out how to improve students' speaking ability in making questions, giving explanations, and answers based on the debate topic. The methodology of this research is a classroom action research which consisted of 3 cycles. The subject of this research was the students of Semester II Sistem Informatika of Informatica Technical Faculty 2019/2020, Potensi Utama University, which consists of 60 students. To collect the data, the researcher applied the observation checklist and fieldnotes. Through the observation checklist, the researchers observed students' activity in the classroom, and by using fieldnotes the researchers summarized the problem during debating process. Based on the research findings, the debate technique which was applied to the subjects of research reflected the improvement of students' speaking ability. Based on the result of the researchers’ observation using the observation checklist and fieldnotes, it can be seen that students' speaking ability in making questions and giving explanations have been improved. The percentage of students' activity in the classroom when debate, in the first cycle, was 42.83%, in the second cycle was 59.17%, and the third cycle was 85.17%. It indicated that debate technique had improved students' speaking ability in making questions and giving explanations.Keywords: Classroom Action Research, College Student, Debate Technique, Speaking Skill